THE ADVISORY IN THE TEACHING OF MATHEMATICS IN DISTANCE EDUCATION, USIG THE WEB CT PLATFORM / LA ASESORÍA EN LA ENSEÑANZA DE LAS MATEMÁTICAS EN LA EDUCACIÓN A DISTANCIA, UTILIZANDO LA PLATAFORMA WEB CT - Ana Rosa Carrillo Avila; Silvia Elena Mota Macias (Didasc@lia: didáctica y educación, 2010)
The university Campus of the North works on a mixed modality and in distance one. Teachers who work with the modality of distance education design their own courses on line; taking into account the instructional design as well as the informative contents, which the students can take to develop the program of the subject. The platform that we use to implement these courses to the technical level and to bachelors in any specialty is the CT Web. This platform accounts for synchronic and asynchrony tools, used for the reception and checking the works done by the students, this is to provide advisory and to ease the knowledge the students are looking for in higher education.